VARIASI LAMA WAKTU FERMENTASI TERHADAP pH, ORGANOLEPTIK DAN KANDUNGAN ANTIOKSIDAN TEH KOMBUCHA DAUN KERSEN DENGAN EKSTRAK MANGGA: Indonesia - haerilindrawan eril (The Journal of Teknologi Pangan, 2022)
Kombucha tea is a beverage that is produced from symbiotic culture activity which is activated in the ingredients used as raw materials by fermentation. This study aims to determine the effect of fermentation time on the pH value, organoleptic and antioxidant content of cherry leaf kombucha tea with mango extract. This study used a completely randomized design (CRD) research method using 1 factor, namely the length of fermentation consisting of 5 treatments with 3 replications in order to obtain 15 experimental units. The results showed the average value of the hedonic test results for the color of kombucha tea ranged from 2.29 to 2.67 which means the color was less favored to preferred, the average value of the pH test of kombucha drinks in a row at P1 to P5 was 4.99, 4.35, 4.11, 3.88 and 3.58, and the antioxidant content of kombucha drink increased with increasing fermentation time. Kombucha drink antioxidant levels ranged from 34.9-36.8%. The best treatment for long fermentation time to produce cherry leaf kombucha drink is 3 days with a characteristic green-brown color, slightly sour fresh taste, a distinctive mango aroma, pH 4.11 and antioxidant content of 36.30%.